The Existence Of Regional Representative Boards In The Indonesian Representative Institution System - Alexander J Sinukaban (Institute Of computer Science (IOCS), 2020)
The Regional Representative Council is a state institution that has a certain structure, position, task and authority by the 1945 Constitution which has been amended. With the presence of this state institution, it also influences and changes the structure of the people's representative institutions in Indonesia, and also the Indonesian state administration system. In the course of the system of Indonesian representative institutions, there was an institution whose duties and capacities were similar to those of the Regional Representatives Council, namely the Senate. Where the Senate was formed during the validity period of the RIS Constitution, along with the development of the Indonesian state administration, this institution was also erased when the Indonesian Constitution returned to the 1945 Constitution. The existence of this institution was replaced with Regional Representatives and Group Delegates, in which they represented regions and groups. certain groups in Indonesia. The first, second, third, and fourth amendments to the 1945 Constitution gave birth to the Regional Representative Council where with this amendment there was a change in the Indonesian state administration system, where with this amendment the People's Consultative Assembly changed both its structure and position, in its structure the People's Consultative Assembly The People's Representative Council consists of the People's Representative Council and the Regional Representative Council, while its position is no longer the highest state institution, but it is equal to the DPR, DPD, President, and other State Institutions as State High Institutions. The Regional Representative Council has similarities with several similar institutions in other countries, namely the Senate (United States) and the State Council (Malaysia) where they already have a strong position in the parliamentary system in their respective countries.The position, duties, rights, and authorities of the Regional Representatives Council in the Indonesian state administration system do not appear to have the same power as the very powerful House of Representatives. This is what invites debate in the existence of the Regional Representative Council. Where the existence of the Regional Representative Council should be improved and given a position and authority that is equal to the Regional Representative Council.